2015
DOI: 10.3892/ol.2015.3755
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting platinum sensitivity in cervical cancer

Abstract: Abstract. The present study aimed to investigate the association between nedaplatin (NDP) sensitivity and the expression of biological factors in cervical cancer. A total of 45 cervical cancer specimens, including 18 pretreatment biopsies and 27 surgical specimens, were used in histoculture drug response assays to determine the chemosensitivity of cervical cancer specimens to NDP. Each specimen was assessed for immunohistochemical expression of Ki-67, p53, B-cell lymphoma-2 (Bcl-2), Bcl-2-associated X protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Bcl-2, an anti-apoptotic protein, is an oncogene that inhibits radiation-or chemotherapy-induced apoptosis (30). Cervical cancers with Bcl-2 expression have been reported to exhibit radiation resistance and poor prognosis (31,32). Bax is a member of the Bcl-2 family and serves a role in enhancing apoptosis (33).…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2, an anti-apoptotic protein, is an oncogene that inhibits radiation-or chemotherapy-induced apoptosis (30). Cervical cancers with Bcl-2 expression have been reported to exhibit radiation resistance and poor prognosis (31,32). Bax is a member of the Bcl-2 family and serves a role in enhancing apoptosis (33).…”
Section: Discussionmentioning
confidence: 99%
“…HPV DNA, E6/E7 mRNA p53, Rb, p16INK4a, telomerase RNA gene (TERC), serum SCC-Ag, OCVA1 [8,[10][11][12][13]15,[20][21][22][23][24][25][26] Markers of cell cycle and proliferation Ki-67, cyclin D1, p53, p63 [12,[26][27][28][29][30][31][32][33][34][35][36] Markers of apoptosis P53, BCL-2, BCL-XL, BAX [10,27,[37][38][39][40][41][42][43][44] Expression of cytokeratins-markers of differentiation CK7, CK8, CK17, CK19 [27,36,37,[45][46][47][48][49] Markers of cell adhesion, invasion and metastasis E-cadherin, P-cadherin, CD44, ADAM9, MT1-MMP, TIMP-1, TIMP-2, MT1-MMP, MMP-2, MMP-1, MMP-9, MMP-14, proMMP-14 furin, gelatinase, TIMP-1 and TIMP-2 [27,[50][51][52]…”
Section: Biomarkers Of Hpv Infection and Carcinogenesismentioning
confidence: 99%
“…According to data, susceptibility to platinum can be predicted by immunostaining for these specific factors in biopsies or surgical specimens before treatment, and expression profiles of these markers may provide additional information for planning individual chemotherapy for cervical cancer. Thus, individualized chemotherapy to maximize the effectiveness of treatment may become clinically valuable in the cases of cervical cancer [41]. Negative correlation of the expression profile of the anti-apoptotic proteins SAG, Bcl-xL, and p53 with the overall survival of patients with cervical cancer stages IIB-IVA has been demonstrated.…”
Section: Markers Of Apoptosismentioning
confidence: 99%
“…Previous studies have indicated elevated COX-2 was strongly related to LNM in stage IB cervical cancer (Kang et al, 2006), the high COX expression has been revealed positive correlation with malignancy in the parametrial tumor tissue or LNM (Ryu et al, 2000). Other studies also found that high-level expression of COX-2 was correlated with a poorer prognosis, recurrence, low sensitivity of nedaplatin, and radiosensitivity (Kim et al, 2003;Chen et al, 2005;Ishikawa et al, 2006;Manchana et al, 2006;Jo et al, 2007;Huang et al, 2013;Stasinopoulos et al, 2013;Kato et al, 2015). In neoplasia, COX-2 stimulates cell proliferation which promotes angiogenesis through pathways involving an increase in VEGF production (Huang et al, 2013;Xu et al, 2014).…”
Section: Introductionmentioning
confidence: 96%